Challenges in Clinical Research in Low and Middle Income Countries: Early Career Cardiologists’ Perspective - Zainab Atiyah Dakhil; F. Aaysha Cader; Amitava Banerjee (Global Heart, 2024)
Despite a growing burden of cardiovascular diseases (CVDs) in Low and Middle Income Countries (LMICs), there remain significant barriers to researchers living in these countries regarding the initiation, progression and completion of research. These obstacles are multifactorial, ranging from a lack of general incentives, national and institutional initiatives and capacity, limited opportunities for funding, and lack of mentorship and support for the presentation and publication of research. In this perspective piece, we highlight some of the challenges we have observed from our experience as early career cardiologists in LMICs and present some potential solutions to address these issues.